Factors Associated with Anxiety, Depression, and Stress Levels in High School Students - Relmu Gedda-Muñoz; Álvaro Fuentez Campos; Alfonso Valenzuela Sakuda; Iván Retamal Torres; Matías Cruz Fuentes; Georgian Badicu; Tomás Herrera-Valenzuela; Pablo Valdés-Badilla (MDPI AG, 2023)
This study aims to investigate the relationship between anxiety, depression, and stress levels with physical activity level and academic performance in high school students; secondly, this study aims to relate and compare anxiety, depression, and stress levels with physical activity level and academic performance. This is a quantitative, descriptive, and comparative cross-sectional study, which evaluated 443 high school students (48% female; 15.13 ± 1.59 years) belonging to the Maule region, Chile. The Depression, Anxiety, and Stress Questionnaire (DASS-21) and the International Physical Activity Questionnaire (IPAQ) were applied. Academic performance was consulted on language, mathematics, and overall grade point average. The results indicate that vigorous physical activity (OR = 0.504; p = 0.017) and high academic performance in mathematics (OR = 0.597; p = 0.027) are associated with a reduced risk of depression. In turn, there is a significant inverse correlation between physical activity with anxiety (r = −0.224; p = 0.000), depression (r = −0.224; p = 0.000) and stress (r = −0.108; p = 0.032), while the performance of mathematics is inversely correlated with depression (r = −0.176; p = 0.000). On the other hand, significant differences (p < 0.05) between anxiety, depression, stress levels, and grade point average were found, with females exhibiting higher scores than males. In conclusion, greater vigorous physical activity and scoring above average in mathematics performance are protective factors against depression.